2019
DOI: 10.1111/febs.14800
|View full text |Cite
|
Sign up to set email alerts
|

The stoichiometry and interactome of the Nucleosome Remodeling and Deacetylase (NuRD) complex are conserved across multiple cell lines

Abstract: The nucleosome remodelling and deacetylase complex (NuRD) is a widely conserved regulator of gene expression. The determination of the subunit composition of the complex and identification of its binding partners are important steps towards understanding its architecture and function. The question of how these properties of the complex vary across different cell types has not been addressed in detail to date. Here, we set up a two‐step purification protocol coupled to liquid chromatography‐tandem mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 73 publications
6
24
0
Order By: Relevance
“…This loss of interaction with CDK2AP1 is most likely caused by deletion of the direct interaction domain. Upon closer inspection of the cross-links between GATAD2A and CHD proteins it is clear that this interaction also requires the C-terminus of the CHD proteins, which is in agreement with data published by the Mackay lab [13,26]. This may explain why the CHD4 1-1627 protein fails to interact with any NuRD complex subunit.…”
Section: Accepted Articlesupporting
confidence: 88%
“…This loss of interaction with CDK2AP1 is most likely caused by deletion of the direct interaction domain. Upon closer inspection of the cross-links between GATAD2A and CHD proteins it is clear that this interaction also requires the C-terminus of the CHD proteins, which is in agreement with data published by the Mackay lab [13,26]. This may explain why the CHD4 1-1627 protein fails to interact with any NuRD complex subunit.…”
Section: Accepted Articlesupporting
confidence: 88%
“…In this study, MTA2 is first identified as a possible target of HOTAIR–miR‐326 regulatory axis in OSCC. MTA2 serves as an important member of the MTA family and contains transcriptional corepressors that function in histone deacetylation 21 . MTA2 is also a component of the Twist complex which inhibits the expression of E‐cadherin 23 .…”
Section: Discussionmentioning
confidence: 99%
“…MTA2 is an important component of the nucleosome remodeling and deacetylase complex, which is conserved across various cell lines and is verified to promote EMT and progression of multiple carcinomas. 21,22 MTA2 is also a part of the Twist complex which can suppress the expression of E-cadherin, 23 and the knockdown of MTA2 inhibits invasion and metastasis of several cancers. 24,25 Therefore, MTA2 may act as a possible set of master coregulatory molecules in OSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins Rbbp7 and Rbbp4 bind histone H4 and most likely have roles as scaffolds (Kloet et al, 2015;Schmidberger et al, 2016). The GATA zinc-finger domain-containing proteins GATAD2A and -B directly interact with MBD2/3 and are also canonical members of the NuRD complex, although their precise function remains to be determined (Sharifi Tabar et al, 2019).…”
Section: Introduction (765 Words)mentioning
confidence: 99%